Accident ahead? Difficulties of drivers with and without reading impairment recognising words and pictograms in variable message signs. (February 2018) - Roca, J.; Tejero, P.; Insa, B.
Abstract: A timely and accurate acquisition of the information provided by variable message signs (VMS) can be crucial while driving. In the current study, we assess the difficulties of adults with dyslexia acquiring the information shown in VMS and provide evidence to discuss the controversial use of pictograms as potential countermeasures. Twenty-two adults with dyslexia and 22 matched controls completed a simulated driving session. The legibility of 12 VMS was assessed, including six text messages (e.g. "ACCIDENT") and six single pictograms (e.g. the icon for "accident ahead"). On average, participants with dyslexia started reading text messages when they were closer to the VMS. In addition, while approaching text VMS, they dedicated more gazes and manifested worse control of speed. Regarding pictogram VMS, we observed no differences in response distance, accuracy, response duration, or number of gazes. To sum up, the evidence provided reveals that adults with dyslexia, despite potential compensation effects, may still find difficulties reading text messages in VMS (shorter legibility distances, longer reading times, and increased cognitive effort), whereas we found no such differences in the recognition of pictograms (only some difficulties keeping a steady speed). Research on inclusive measures to improve reading in low-skilled or dyslexic drivers must be encouraged. Highlights: Dyslexic adults can still find difficulties reading text in variable message signs. Shorter legibility distances are reported for text messages. No significant differences were found in the recognition of pictogram messages. However, increased cognitive effort is observed with both text and pictograms. Research on inclusive measures to improve reading in dyslexic drivers is encouraged.